2012
DOI: 10.1002/jmv.23508
|View full text |Cite
|
Sign up to set email alerts
|

Does high viral load of hepatitis E virus influence the severity and prognosis of acute liver failure during pregnancy?

Abstract: The incidence and mortality in pregnant women with acute liver failure caused by hepatitis E virus (HEV) is high. Data on the viral load of HEV during pregnancy are limited. The study was designed to determine the viral load of HEV and its association with the disease severity in patients with acute liver failure. A total of HEV related 163 patients with acute liver failure which included 105 pregnant, 46 non-pregnant women and girls and 12 men and 730 patients with acute viral hepatitis which comprised of 220… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 31 publications
2
35
0
Order By: Relevance
“…Nevertheless, these cases do not indicate a comparable severe outcome of gt3 infections during pregnancy. Of note, high viral loads of HEV during pregnancy have been implicated as one of the factors responsible for the severity of the infection during pregnancy 48, 49. JEG‐3 cells allowed HEV viral particle production with membrane‐associated extracellular viral particles and biophysical properties comparable to human liver cell‐derived viruses (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these cases do not indicate a comparable severe outcome of gt3 infections during pregnancy. Of note, high viral loads of HEV during pregnancy have been implicated as one of the factors responsible for the severity of the infection during pregnancy 48, 49. JEG‐3 cells allowed HEV viral particle production with membrane‐associated extracellular viral particles and biophysical properties comparable to human liver cell‐derived viruses (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A study from North India reported a correlation of viral load with increased severity of infection during pregnancy. 75 In this study, the HEV viral load in ALF pregnant women was 5.87 Â 10 4 AE 1.5 Â 10 5 mL/mL as compared to AVH pregnant women 343.29 AE 216.44 mL/mL. The viral load in ALF and AVH in non-pregnant women was 199.2 AE 225.5 mL/mL and 13.83 AE 7.8 mL/mL, respectively.…”
Section: Viral Factorsmentioning
confidence: 47%
“…However, pregnant women with acute HEV infection are at risk for fulminant hepatitis, liver failure, and high maternal mortality and morbidity rates. 7,29 In an attempt to identify causes associated with this high mortality rate of HEV, Borkakoti and colleagues 29 found that the viral loads of HEV in pregnant women with ALF were significantly higher than those in nonpregnant women.…”
Section: Viral Infectionsmentioning
confidence: 99%